Multiple sclerosis: Association to HLA DQ? in a tropical population (1999)
Studies performed in subtropical populations have found significant association between the phenotype multiple sclerosis (MS) and the major histocompatibility complex (MHC). We present the results of a case-control study conducted on a tropical population (Antioquia, Colombia) in order to detect a possible association between MS and HLA DQ? (HLA DQA1*) alleles. Forty chromosomes belonging to MS patients were compared to two sets of controls (40 and 910 chromosomes, respectively). The HLA DQA1*0101 and DQA1*0102 alleles were found in a significantly higher proportion among the cases than among the controls, whereas the HLA DQA1*0103 allele was found in a significantly lower proportion of the cases. These results suggest that the association of HLA DQA1*0101, DQA1*0102 and DQA1*0103 to the MS phenotype found in Caucasian subtropical populations remains in individuals with MS inhabiting the tropics. This finding could mean that the major genetic component associated to the MHC in subtropical populations is the same in the tropics.